COPING ANG PSYCHOLOGICAL ADAPTATION IN PARENTS OF CHILDREN WITH CLEFT PALATE - Limiñana Gras, Rosa María; Corbalán Berná, Francisco Javier; Patró Hernández, Rosa (Anales de Psicología / Annals of Psychology, 2007)
The unexpected birth of a son with a chronic malformation such as cleft and lip palate has an enormous impact on family dynamics and the psychological organization of the parents. This study tries to give account of some of these aspects in a sample of 36 parents of children with a diagnosis of cleft lip and palate. Coping strategies in these parents and their personality styles, allow us to describe stable ways of response on individuals that can be excellent indicators of the way in which parents confront this new reality, as well as of its effects on the medium and long terms.